Primary pyogenic ventriculitis caused by Neisseria meningitidis: case report and review of the literature. (31st January 2017) - Gronthoud, Firza; Hassan, Ibrahim; Newton, Pippa
Abstract : Background. Pyogenic ventriculitis is a well-known complication of meningitis, brain abscesses and intraventricular drains. Primary pyogenic ventriculitis is a rare entity and few cases have been described so far. We report the first case of primary pyogenic ventriculitis in an adult caused by Neisseria meningitidis and present an overview of all reported adult primary pyogenic ventriculitis cases in the English literature. Methods. A PubMed search was performed using the terms ependymitis, ventricular empyema, pyocephalus and ventriculitis. Filter was set for adults and English. Articles in which pyogenic ventriculitis was a complication of well-known risk factors were excluded. A total of five cases of primary pyogenic ventriculitis were identified. Results. There were seven adult patients. Only one patient showed signs of meningeal irritation. Four patients had positive blood cultures with Escherichia coli (one patient), methicillin-resistant Staphylococcus aureus (one patient), one patient was bacteraemic with Enterococcus faecalis, Escherichia coli and Peptostreptococcus spp., and N. meningitidis (our patient). In four patients cerebrospinal fluid was sent for culture, which yielded methicillin-sensitive Staphylococcus aureus (one patient), Peptostreptococcus spp. (one patient), Streptococcus intermedius (one patient, identified via 16S PCR) and Listeria monocytogenes (one patient). Cerebrospinal fluid cell count was determined in four patients and showed pleocytosis in all four cases. Ventricular drainage was performed in four patients. Five patients survived. Discussion. We report the first case of pyogenic ventriculitis caused by N. meningitidis . Primary pyogenic ventriculitis is a rare entity with various clinical presentations caused by various bacterial species. Treatment consists of adequate antimicrobial therapy, and ventricular drainage may be necessary.